Juridical Analysis of Contract Work Agreements For Honorary Employees and The Right To Obtain Employment and A Decent Livelihood For Humanity : (A Study of Honorary Employees In The Environment of Lambung Mangkurat University, Banjarmasin) - Zainul Akhyar; Muhammad Elmy; Maritatul Kiptiah (Badan Penerbit STIEPARI Press, 2024)
The issue of contract workers emerged following the enactment of Law Number 5 of 2014 regarding State Civil Apparatus and Government Regulation Number 49 of 2018, which implied the termination of contract workers in government agencies. The objectives of this research are: 1. To understand the process and content of employment agreements signed by the parties, reviewed from a juridical aspect for contract workers in the ULM environment. 2. To determine the right to work and obtain decent income for humanity for contract workers in the ULM environment from a juridical aspect, and 3. To identify legal protection efforts for contract workers in ensuring future employment status in the ULM environment. This research is a normative legal study with a qualitative research paradigm. The research sample was randomly selected among contract workers to obtain credible data. Data collection techniques include documentary studies to gather legal materials, followed by interview techniques to gather empirical data. The results of the study found that the future employment status of contract workers is still unclear from the process and content of the employment agreement. However, contract workers still exist factually. The income earned by contract workers is still below the minimum wage standard due to the absence of regulations on remuneration and salary disbursement based solely on the financial budget capacity, resulting in income that is insufficient to meet the standard of decent living. Furthermore, legal protection efforts for contract workers were not found juridically related to the certainty of future employment. Based on the results of this study, it is recommended to various stakeholders to address the issue of the future status of contract workers working in government agencies in order to avoid social, political, legal, and economic upheavals, namely: (1) creating new regulations in the form of Government Regulations. Legal approaches to addressing contract worker issues are the best way to achieve justice and humanity. (2) every agency needs to take policy measures to address contract workers in the form of contract extensions while awaiting the issuance of Government Regulations (PP) governing the future employment status of contract workers. This is intended to provide certainty that can create a peaceful working environment for contract workers.